An “initial-engineering-end use” quasi-market pricing mechanism under cascading risk for cross-regional water rights trading - Xuxia Li; Huimin Wang; Gang Liu; Liu Yang; Zhou Fang; Yi Xiao; Xiaoying Lai; Li Gao; Ying Teng (Agricultural Water Management)
Water rights trading within a market economy has emerged as an effective solution for enhancing water use efficiency and addressing water scarcity. However, the development of a pricing mechanism that accounts for the spatial heterogeneity of water resources remains a critical challenge. This study proposes an “initial-engineering-end use” quasi-market pricing mechanism based on empirical research of cross-regional water rights trading in Pingxiang, Jiangxi, China. The mechanism comprises three stages, each designed to address specific risks. To support these stages, data from field studies is used to calibrate three unique pricing models: the stochastic differential game, incomplete contract theory, and the Nash-bargaining model. We analyze the interactions among equilibrium water prices across these stages to explore the cascade effects. In Pingxiang, the local government has successfully adopted and implemented this mechanism. Empirical results and practical applications reveal several key findings. (1) A comparative analysis of national governance across different countries indicates that the quasi-market pricing mechanism effectively determines end use water prices in China. (2) Initial corporate and government investments mitigate trading risks and enhance stability. (3) Overlooking ecosystem service value leads to the undervaluation of initial and end use water prices. (4) Practical applications of the proposed mechanism in Inner Mongolia, China, and the Murray-Darling Basin, Australia, demonstrate that end use water prices are generally higher in water-scarce regions. Overall, this study provides a practical and adaptable approach for pricing cross-regional water rights trading, applicable to both water-rich and water-scarce regions globally.